Ответы и объяснения

Лучший Ответ!
2013-07-29T15:29:31+00:00
№ 3.
1. 2m/2m+n - 4m^2/4m^2+4mn+n^2 = 2m/2m+n - 4m^2/(2m+n)^2 = 4m^2+2mn-4m^2/(2m+n)^2=2mn/(2m+n)^2
2. 2m/4m^2-n^2 + 1/n-2m = 2m/(2m+n)(2m-n) - 1/2m-n = 2m-2m-n/(2m+n)(2m-n) = -n/(2m-n)(2m+n)
3. -2mn*(2m-n)(2m+n)/(2m+n)^2*n = -2m(2m-n)/2m+n = -4m^2+2m/2m+n
№ 4.
-2x^2-7x+4=сократим на -2=x^2+3.5x-4
Решим уравнение:
x^2+3.5x-4=0
D=b^2-4ac=12.25+8=20.25
x1=-b+корень из D/2a=-3.5+4.5/2=1/2=0.5
x2=-b-корень из D/2a=-3.5-4.5/2=-4
Таким образом, -2x^2-7x+4=(х+4)(х-0,5)
№ 5.
Разложим числитель дроби.
3x^2-14x-5=0
D=b^2-4ac=196+60=256
x1=-b+корень из D/2a=14+16/6=5
x2=-b-корень из D/2a=14-16/2=-2/6=-1/3
3x^2-14x-5=((х-5)(х+1/3)
Разложим знаменатель дроби.
4x^2-21x+5=0
D=b^2-4ac=441-80=361
x1=-b+корень из D/2a=21+19/8=5
x2=-b-корень из D/2a=21-19/8=2/8=1/4
4x^2-21x+5=(х-5)(х-1/4)
Таким образом, 3X^2-14x-5/4x^2-21x+5 = (х-5)(х+1/3)/(х-5)(х-1/4) = х+1/3 / х-1/4